IMPLEMENTASI MANAJEMEN KEARSIPAN BERBASIS DIGITAL UNTUK MENDUKUNG PELAYANAN PRIMA DI SMA NEGERI 12 SEMARANG - Haskia Pratama Putra Budi Utomo; Nina Oktarina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of information technology has encouraged educational institutions to transform their administrative management systems, including in the field of records management. Conventional archive management is considered inefficient and potentially hinders the quality of administrative services. This study aims to analyze the implementation of digital-based records management in supporting excellent administrative services at SMA Negeri 12 Semarang.This research employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The research subjects include the head of administration and administrative staff directly involved in managing school records. The findings indicate that the implementation of digital records management improves work efficiency, accelerates document retrieval processes, and enhances the quality of administrative services. However, several challenges remain, including limited training, uneven infrastructure readiness, and the absence of formally established standard operating procedures. This study concludes that digital-based records management contributes positively to excellent service in schools when supported by adequate human resources, infrastructure, and clear institutional policies. The contribution of this research lies in strengthening empirical evidence regarding the importance of archive digitalization in supporting administrative services within educational institutions.